2016
DOI: 10.1016/j.mce.2016.08.046
|View full text |Cite|
|
Sign up to set email alerts
|

Transplantation of alginate-encapsulated seminiferous tubules and interstitial tissue into adult rats: Leydig stem cell differentiation in vivo?

Abstract: In vivo and in vitro studies were conducted to determine whether testosterone-producing Leydig cells are able to develop from cells associated with rat seminiferous tubules, interstitium, or both. Adult rat seminiferous tubules and interstitium were isolated, encapsulated separately in alginate, and implanted subcutaneously into castrated rats. With implanted tubules, serum testosterone increased through two months. Tubules removed from the implanted rats and incubated with LH produced testosterone, and cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…SLCs have been shown to be capable of giving rise to testosterone-producing Leydig cells in vivo, in locations outside testis (Chen et al, 2016). This could have clinical implications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SLCs have been shown to be capable of giving rise to testosterone-producing Leydig cells in vivo, in locations outside testis (Chen et al, 2016). This could have clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…For example, if niche factors from the tubules were required for SLC proliferation and/or differentiation, such factors would not be present in preparations of interstitial tissue cultured in the absence of the tubules. To examine this possibility, we carried out a co-culture experiment in which the tubules and interstitial tissues were cultured in separate chambers that allowed a free exchange of paracrine factors between the two tissues (Chen et al, 2016). The co-culture of the interstitium with seminiferous tubules resulted in the production of testosterone-producing Leydig cells in the interstitial tissue.…”
Section: Stem Leydig Cells In Prepubertal and Adult Testesmentioning
confidence: 99%
“…The rodent testis contains SLCs that can form new Leydig cells and restore serum testosterone concentrations when differentiated Leydig cells are removed (Chen et al , 2016; Li et al , 2016). Our current results show that adult rSLCs are also able to differentiate into other non-Leydig cell types in vivo , in this case, prostatic and uterine epithelium, when exposed to appropriate inductive cues from fetal/neonatal mouse mesenchyme from other tissues.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a previous study has shown that nestin-positive SLCs from neonatal mice can be programmed in vitro to form tissues of endodermal, mesodermal and ectodermal origin (Jiang et al , 2014). This may be due to age, experimental conditions ( in vitro vs in vivo ) and/or species of the SLCs used, since Jiang et al used neonatal mouse SLCs, in contrast to our adult rat SLCs (Stanley et al , 2012; Chen et al , 2016; Li et al , 2016). Previous studies have shown that the ability of differentiated epithelium to transdifferentiate decreases with age (Cunha, 1975; 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Other disease models have also used alginate microencapsulation for therapeutic use of xenogeneic stem cell-delivery. Researchers have reported functional alginate encapsulated adrenal SCs for use in adrenal hormone insufficiency diseases [63,64]. Successful alginate encapsulation of neural embryonic stem cells was also reported for targeted cell-delivery serving possible treatment for neural tissue repair in several neurological disorders [65].…”
Section: Stem Cell-delivery Systemmentioning
confidence: 99%